EKSPLORASI NILAI TRADISI MUSIK PATROL SEBAGAI PENINGKATAN NILAI KARAKTER SISWA PADA PEMBELAJARAN IPS - Fatdriatun Ismah; Siti Asiyah; Dina Mustaqimah; Nindia farah Az Zahro; Alfisyah Nurhayati (Institut Agama Islam Negeri Ponorogo, 2023)
This study aims to explore and find out the values ​​in the Patrol Music tradition in Gebang. develop potential and collaboration between education and patrol music values. This illustrates the effectiveness of a learning method using one of the media, namely traditional music, besides focusing on collaboration but also with the aim of maintaining tradition so that it is maintained in the times of development. The use of musical culture is observed using qualitative methods where this research produces information through observation, interviews. The results of the study show that the values ​​of patrol music can be applied in the social studies learning process, which can be seen from the existence of togetherness values ​​that are always fostered by community members. Keywords: Patrol Music, Character, Values